(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Linguistic analysis of S. Eraliev’s poetry opens the way to a deep understanding of the poetic capabilities of the Kyrgyz language through the study of its vocabulary, syntax, metaphors and stylistic features.